Fast Neutrons Shielding Properties for HAP-Fe2O3 Composite Materials - BOODAGHİ MALİDARRE, Roya and AKKURT, İskender and GUNOGLU , Kadir and AKYILDIRIM, Hakan (International Journal of Computational and Experimental Science and Engineering, 2021)
Neutron has been one of the most interesting particle since its discovery. Being an uncharged particle it is more difficult to shield in comparison with the other radiation types. This may be due to the differences of its interaction with matter. The main interaction processes of neutron with a matter may be via (n,p) reaction and thus hydrogenous materials are generally preferred to shield neutron. In this study neutron shielding properties for HAP composites have been investigated. This is done using Phy-X/PSD software.